Associations between drug use and sexual risks among heterosexual men in the Philippines. (December 2013) - Regan, Rotrease; Dyer, Typhanye Penniman; Gooding, Taigy; Morisky, Donald E
The relationship between drug use and sexual risk behaviours among 2272 men in the southern Philippines was assessed. Over 20% of participants used drugs. Logistic regression analyses adjusted for age, marital status, income, occupation and geographic region revealed that compared to non-drug users, men who used drugs had earlier sexual debuts (adjusted odds ratio = 1.73; 95% confidence interval = 1.38–2.17), were more likely to report two or more recent sexual partners (adjusted odds ratio = 2.22; 95% confidence interval = 1.59–3.11), and were more likely to report ever having sex with a female sex worker (adjusted odds ratio = 2.99; 95% confidence interval = 2.25–4.00). Condom use was noted to be low overall among the men in this study; however, the odds of more frequent condom use with a regular partner were greater for men who used drugs compared to non-drug users (adjusted odds ratio = 1.60; 95% confidence interval = 1.26–2.02). There were no significant differences in condom use during last sex or frequency of condom use with a sex worker. While injection drug use was not common (1%), use of oral or inhaled substances was prevalent, and associated with increased sexual risk for acquisition and transmission of STI/HIV. Efforts to decrease STI/HIV transmission should specifically target non-injection drug use as a risk factor.